2022
DOI: 10.1021/acsenergylett.2c01969
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Transparent Radiative Cooler Designed by Quantum Computing

Abstract: Transparent radiative coolers can be used as window materials to reduce cooling energy needs for buildings and automobiles, which may contribute significantly to addressing climate change challenges. However, it is difficult to achieve high visible transparency and radiative cooling performance simultaneously. Here, we design a visually transparent radiative cooler on the basis of layered photonic structures using a quantum computing-assisted active learning scheme, which combines active data production, machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…A daytime radiative cooler (DRC), first proposed by Raman, consumes no electricity to reduce the temperature of objects below that of ambient air, the so-called subambient cooling, by strongly reflecting the solar irradiance at λ = 0.3–2.5 μm and simultaneously radiating heat out to the extremely cold universe through an atmospheric transparency window at λ = 8–13 μm . A variety of DRCs have been demonstrated, which are promising for potential applications in energy-efficient buildings, , photovoltaic modules, and personal thermal management . However, the majority of the proposed DRC materials exhibit white or metallic colors to guarantee a strong reflection of the solar irradiance, which is unfavorable in some application scenarios and installation locations such as building envelopes and vehicles for aesthetic purposes and potentially leads to light pollution and eye safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…A daytime radiative cooler (DRC), first proposed by Raman, consumes no electricity to reduce the temperature of objects below that of ambient air, the so-called subambient cooling, by strongly reflecting the solar irradiance at λ = 0.3–2.5 μm and simultaneously radiating heat out to the extremely cold universe through an atmospheric transparency window at λ = 8–13 μm . A variety of DRCs have been demonstrated, which are promising for potential applications in energy-efficient buildings, , photovoltaic modules, and personal thermal management . However, the majority of the proposed DRC materials exhibit white or metallic colors to guarantee a strong reflection of the solar irradiance, which is unfavorable in some application scenarios and installation locations such as building envelopes and vehicles for aesthetic purposes and potentially leads to light pollution and eye safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…To date, much attention has been paid to accomplishing wavelength-selective thermal emission, which supports the development of thermophotovoltaics, ,,, radiative coolers, ,, , and infrared camouflaging . In the era of carbon neutrality, radiative coolers are garnering increasing popularity because they do not consume external energy for cooling , and are formed as scalable thin films. , In addition, their practical function can be adaptively switched between cooling and heating with the use of temperature-triggered emissivity-changing materials ( e.g.…”
mentioning
confidence: 99%
“…To date, much attention has been paid to accomplishing wavelength-selective thermal emission, which supports the development of thermophotovoltaics, ,,, radiative coolers, ,, , and infrared camouflaging . In the era of carbon neutrality, radiative coolers are garnering increasing popularity because they do not consume external energy for cooling , and are formed as scalable thin films. , In addition, their practical function can be adaptively switched between cooling and heating with the use of temperature-triggered emissivity-changing materials ( e.g. , vanadium oxide) to override excessive cooling in cold settings. , In comparison, angle-selective thermal emission is more challenging because of the complexity of design principles. , For example, Greffet et al reported narrow-angle emission at a single thermal wavelength (11.36 μm) in the p polarization by constructing a one-dimensional (1D) wavelength-scale grating (6.25 μm in pitch) on a SiC substrate .…”
mentioning
confidence: 99%
See 2 more Smart Citations